Kumpulan Soal Argumentasi Berpola Claim, Data, Warrant (CDW) - Lailatul Hairi; Muhammad Haris Effendi Hasibuan (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to find out the effectiveness of product collection of items about argumentation pattern claim, data, and warrant against the arguments of students in the subjects of biology respiratory system material at SMA IX Negeri 2 Jambi City. This research uses ADDIE model (Analysis, Desaign, Development, Implementation, and Evaluation). Data collection methods used in this research are interview methods, questionnaires, and tests. The results showed the development of a collection of questions in sma negeri 2 jambi school with 10 questions and 6 respondents who gave pretest and posttest questions, then got a pretest result of 1.23 and a posttest average score of 3.75. Based on t paired test sample t tests obtained sig. (2-tailed) of 0.000< 0.05 then H0 rejected and Ha received, there is an influence on the collection of points of argumentation on the ability of students argumentation in SMA Negeri 2 Jambi City. In conclusion, the product of a collection of argument-patterned claims, data, and warrants (SDW) developed influenced the argumentation of students in the subjects of respiratory system material biology at SMA IX Negeri 2 Jambi City. Keywords: Arguments, Problem Sets, Claim Patterns, Data, Warrant (CDW)